The Relationship Between Self-Efficacy and Career Decision Making in Students at Senior High School : Hubungan Antara Self Efficacy dengan Pengambilan Keputusan Karir pada Siswa di Sekolah Menengah Atas - Cici Dwi Iswanti; Zaki Nur Fahmawati (Academia Open, 2022)
This study aims to determine the relationship between self-efficacy and career decision making in students at SMK Pharmacy Cendekia Medika Nusantara Pandaan. The hypothesis proposed by the researcher is that there is a positive relationship between self-efficacy and career decision making in students at SMK Pharmacy Cendekia Medika Nusantara Pandaan. The quantitative method was chosen by the researcher to achieve the objectives of this study. Respondents in this study used a saturated sample by using the entire population to be used as a research sample. This study uses a self-efficacy scale and a career decision-making scale with reliability 0,819 and 0,767. The results of the product moment showed that the rxy correlation coefficient was 0.354 with a significance of 0.001 (P <0.05), meaning that there was a significant positive relationship between self-efficacy and career decision making in students at the Mdika Nusantara Pandaan Pharmacy Scholar Vocational School. The effective contribution of self efficacy 12,5% towards career decision making. This means that there are 87,5% of other factors that influence outside the self-efficacy. Highlights: Positive relationship: The study establishes a positive correlation between self-efficacy and career decision making in students, suggesting that higher self-efficacy levels are associated with better career decision-making abilities. Quantitative method: The researcher employs a quantitative approach to gather and analyze data, providing numerical evidence for the relationship between self-efficacy and career decision making. Saturated sample: The study utilizes a saturated sample, involving the entire population of students at SMK Pharmacy Cendekia Medika Nusantara Pandaan, ensuring comprehensive representation for the research findings. Keywords: self-efficacy, career decision making, vocational school, relationship, students